The Nexus of Energy, Finance, Governance and Remittances with Economic Complexity and Ecological Footprints in SAARC Economies - Pria, Nusrat Jahan; Alam, Md Jobayer; Hurira, Abu; Rana, Md Juyel; Kamrujjaman, Md; Akhter, SM Rukaya; Dewan, Md. Farid; Kibria, Md. Golam; Hossain, Imran (International Journal of Energy Economics and Policy, 2026)
This assessment delves into the intensity of SAARC’s government effectiveness, financial development, renewable energy, remittances, and GDP on the country’s ecological footprint and economic complexity. Data applied to the economic complexity (EC) and ecological footprint (EFP) model covers 1995–2021. Judging by the Discoll-Kraay Standard Error analysis, financial development itself and its indices, including financial Institutions and the financial market amplifies ecological footprint and economic complexity in the SAARC economies but unfortunately, elevation of ecological footprint is undesirable for the environment. Nevertheless, the economic complexity and ecological impact of SAARC are being heightened by government effectiveness, remittances, and GDP. Renewable energy increases economic complexity, despite its reduced EFP. Moreover, the interactions among government effectiveness, remittance and financial development have a positive influence on the both models. Evidently, the validity and credibility of the findings are confirmed by the Panel-Corrected Standard Errors (PCSE) and Feasible Generalized Least Squares (FGLS) model. The authority should continue stable financial institution and market, proper allocation of remittances, effective government duties to make sustainable economic enhancement.